2005
DOI: 10.2166/wst.2005.0518
|View full text |Cite
|
Sign up to set email alerts
|

Environmental aspects of the anaerobic digestion of the organic fraction of municipal solid wastes and of solid agricultural wastes

Abstract: In order to obtain more detailed information for better decision making in future biogenic waste treatment, different processes to treat biogenic wastes in plants with a treatment capacity of 10,000 tons of organic household wastes per year as well as agricultural codigestion plants were compared by life cycle assessments (LCA). With the tool EcoIndicator, anaerobic digestion is shown to be advantageous as compared to composting, incineration or a combination of digestion and composting, mainly because of a be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 0 publications
0
24
0
1
Order By: Relevance
“…Particular analyses evaluating impacts on the environment in recent years has shown the use of biogas for production of electric energy and heat produces less greenhouse gases than the use of fossil fuels (Borjesson and Berglund 2006;Edelmann at al., 2005;Jury et al, 2010;Kimming et al, 2011). A question in this case is whether it is possible to use arable land for agricultural production as input source for production of electricity in biogas stations.…”
Section: Resultsmentioning
confidence: 99%
“…Particular analyses evaluating impacts on the environment in recent years has shown the use of biogas for production of electric energy and heat produces less greenhouse gases than the use of fossil fuels (Borjesson and Berglund 2006;Edelmann at al., 2005;Jury et al, 2010;Kimming et al, 2011). A question in this case is whether it is possible to use arable land for agricultural production as input source for production of electricity in biogas stations.…”
Section: Resultsmentioning
confidence: 99%
“…However, LCA studies have shown that AD of MSW reduces environmental impacts and is more cost -effective (in Europe) on a whole system basis than composting or landfilling options [86,87].…”
Section: Ad Systems Generally Have Four Classifications [80]mentioning
confidence: 99%
“…Furthermore, another motivation to apply AD to treat the waste is that the producers can acquire emission reduction (CER) credits by clean development mechanism (CDM) defined in the Kyoto Protocol (International Panel on Climate Change (IPCC) Guidelines, 2006;Tong and Jaafar, 2006). Besides the environmental benefits of waste treatment (Edelmann et al, 2005), government agencies and private companies have extensively invested in AD technologies due to the increasing energy demand and environmental concerns such as global warming. Emphasis is mainly given to increase the generation of biogas, accomplish better rate of breakdown in the reactor, and subsequently minimized organic waste residue (Sonesson et al, 2000) to make the process economical.…”
Section: Introductionmentioning
confidence: 99%